Characterization of two members of the rho gene family from the yeast Saccharomyces cerevisiae. - Madaule, P (1987)
The rho genes comprise an evolutionarily conserved family with significant homology to the ras oncogene family. Two members of the rho family were isolated from the yeast Saccharomyces cerevisiae and characterized by DNA sequence analysis. The yeast genes RHO1 and RHO2 are 70% and 57% identical, respectively, to the rho gene of the marine snail Aplysia, and they are 53% identical to each other. Inactivation of these genes showed that RHO1 is required for cell viability, while RHO2 is not an essential gene. A mutant allele of RHO1 (RHO1-His68) was constructed with a mutation analogous to one that activates the transforming potential of the human HRAS gene. Diploid strains containing RHO1-His68 in either low or high copy number are unable to sporulate, and the mutant allele is dominant over wild-type RHO1. The requirement for RHO1 cannot be circumvented by introduction of high copy number plasmids containing either the gene encoding the catalytic subunit of cAMP-dependent protein kinase or the mutant allele RAS2-Val19. Despite the conservation between the rho and ras gene families, the finding that RHO1 functions independently of the adenylate cyclase cAMP-dependent protein kinase cascade suggests that rho and ras are involved in distinct biochemical pathways.